2005
DOI: 10.1074/jbc.m502060200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent Kinase Inhibitors and JNK Act as Molecular Switches, Regulating the Choice between Growth Arrest and Apoptosis Induced by Galectin-8

Abstract: Galectin-8, a mammalian ␤-galactoside binding lectin, functions as an extracellular matrix protein that forms high affinity interactions with integrins. Here we demonstrated that soluble galectin-8 inhibits cell cycle progression and induces growth arrest. These effects cannot be attributed to interference with cell adhesion but can be attributed to a 4 -5-fold increase in the cellular content of the cyclin-dependent kinase inhibitor p21, which was already evident following a 4-h incubation of H1299 cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 64 publications
1
40
0
1
Order By: Relevance
“…Recent studies reported that soluble galectin-8 inhibits growth of human nonsmall cell lung carcinoma cells. 21 Therefore, we studied in the next step the effect of recombinant mutant form…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that soluble galectin-8 inhibits growth of human nonsmall cell lung carcinoma cells. 21 Therefore, we studied in the next step the effect of recombinant mutant form…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is consistent with a number of studies connecting p21 expression with MAPK/JNK signaling. 49,50 Since our reporter gene studies demonstrated a clear involvement of FHL2 in MAPK-dependent signaling and identified it as an important transcriptional cofactor for the MAPK effector c-jun, we conclude that FHL2 is required for MAPK-dependent upregulation of p21. One important question concerning the function of overexpressed FHL2 in breast cancer is whether FHL2 contributes to tumor suppression or to tumor progression.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…The LGALS8 can inhibit cell adhesion and cell cycle progression and induce growth arrest or apoptosis (59,60). During the early phase of differentiation, the CDX2 signal from the LGALS8 DNA increased (Fig.…”
Section: Cdx2 Is a Central Node In The Intestinal Transcription Factormentioning
confidence: 99%